ANAEROBIC PERFORMANCE ON WINGATE TEST OF REGULAR USERS OF MONOPHASIC ORAL CONTRACEPTIVE IS NOT INLFUENCED BY MENTRUAL CYCLE PHASE. (Fiep Bulletin - online, 2014)
It has been suggested that energy transformation during exercise is influenced by hormonal variations of menstrual cycle phases what could affect exercise performance. Oral contraceptive (OC) abrogates hormonal variations and may reduce menstrual cycle phase effects on exercise performance. So the present study evaluated the anaerobic performance of regular users of OC on the Wingate test. Six health women (mean age 24.17 ± 1.94 years, mean high 1.65 ± 0.01m, mean body mass 63.17 ± 7.18kg), monophasic OC users for at least 6 continuous months were submitted to the Wingate test at three phases of menstrual cycle:  at the end of 1st week (days 5-7) and 3rd week (days 19-21) and at the end of interval week (days 26-28) of OC usage. During the Wingate test the following parameters were analyzed: relative maximum anaerobic power output (W/kg), maximum anaerobic power output (W) and fatigue index (%). Pre- and post-exercise serum lactate and glucose levels were also measured.Data obtained have demonstrated no variations on anaerobic performance of regular OC users, comparing relative maximum anaerobic power output, mean anaerobic power out put and fatigue index in the three different phases of the menstrual cycle phase evaluated (p
Keywords: menstrual cycle; oral contraceptive; anaerobic performance